If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y = -3 + -1x Solving -3y = -3 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-3'. y = 1 + 0.3333333333x Simplifying y = 1 + 0.3333333333x
| 4.5(r-4)=-3(r-1.5) | | .05x+.13(x-3)=.2(x-2) | | 3x-8=6x+1 | | 3h^2+5h/h | | 48-6/3*2=7 | | X^2-2mx+1=0 | | 48-6/3*2= | | 1.2x+6=30 | | 35-5(2x+3)= | | b^2+64=0 | | 36x^2+344x-160=0 | | 2x+11=-13 | | X^2=25/36 | | 2x^2+13a-7=0 | | 10x-3(8-5x)= | | -8c-1=-3 | | 3ay^2+9a=0 | | X^2=74 | | 13-(3-n)=5(n+2) | | -4=2(1+3r)+2(r-3) | | X^2=123 | | x^2+8x-8y+24=0 | | 17x-3(4+5x)= | | 3y^3=648 | | x+(16/x)=8 | | 99=5x-1 | | 13-(3-n)=5(n-2) | | 7x-(2x+8)= | | 7a+3a=-2 | | 23-2c=49 | | 6a^3-8a^2+3a-4=0 | | 8x^3+2x^7= |